Analysis of possibility of virtual reality usage for investigating reaction on given conditions - Łukasiak, Marcin; Machul, Kamil; Maj, Mateusz (Journal of Computer Sciences Institute, 2019)
The study was tend to checking the possibility of using VR technology to invoke specific emotions on the subject. Literature studies have shown a high probability of obtaining successful results, but so far studies have been based on measurements obtained using specialized, expensive equipment. This study was about to show that obtaining similar results is also possible with usage of low budget solutions. Received results allow to conclude even using the less sophisticated technology, satisfactory results can be gained, which can determine the effect of the image displayed in the goggles on the emotions of the subject.